2013
DOI: 10.1002/jrs.4308
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic studies of LixSiy compounds

Abstract: The phase diagram of the Li–Si system contains several phases with Li and Si in well defined ratios. So far, only the Raman spectrum of LiSi has been reported. In this work, we present experimental Raman scattering results for the crystalline lithium silicide phases Li12Si7, Li7Si3, Li13Si4, and Li21Si5/Li22Si5, which show clearly distinguishable Raman modes. The experimental results are compared with theoretical data obtained by density functional theory calculations. Copyright © 2013 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Starting from the metallic-conductive lithium, all studied silicides possess a finite γ value, which decreases with increasing silicon content indicating a decrease in the electrical conductivity in the sequence Li 17 Si 4 to Li 12 Si 7 . This result is in accordance with the literature[42][43][44].…”
supporting
confidence: 95%
“…Starting from the metallic-conductive lithium, all studied silicides possess a finite γ value, which decreases with increasing silicon content indicating a decrease in the electrical conductivity in the sequence Li 17 Si 4 to Li 12 Si 7 . This result is in accordance with the literature[42][43][44].…”
supporting
confidence: 95%
“…[14,81] Gruber et al reported the comparison of Raman signals for diverse phases of lithium silicide (Li 12 Si 7 , Li 7 Si 3 , and Li 13 Si 4 ). [83] From the in-situ Raman spectrum, the sharp SiÀSi peak decreases gradually and is shifted and broadened but is not removed completely during first lithiation, as shown in Figure 11b-II. This implies that the core Si remains unreacted, whereas the outer Si layers are transformed into amorphous lithium silicide.…”
Section: Raman Spectroscopymentioning
confidence: 96%
“…According to the literature, the peak that appears at approximately 516 cm −1 in the spectrum is associated with the Si−Si stretching mode in crystalline Si (amorphous Si has a broad peak from 480 to 520 cm −1 ) along with the D‐band and G‐band (1350 and 1580 cm −1 , respectively), which corresponds with the carbon in a Si/C mixture ,. Gruber et al reported the comparison of Raman signals for diverse phases of lithium silicide (Li 12 Si 7 , Li 7 Si 3 , and Li 13 Si 4 ) …”
Section: Analytic Approach For Nanostructured Simentioning
confidence: 99%
“…The expermental results were compared with theoretical data obtained from DFT calculations. [229] Heyns and Harden reported the temperature dependence of the Raman spectra of chromium-doped titanite (CaTiOSiO 4 ). No evidence could be found of the existence of other ions, such as Cr 4+ ions in Ti-sites, in the Raman spectra using different laser lines to excite the spectra.…”
Section: Single Crystalsmentioning
confidence: 99%
“…Gruber and coworkers present Raman scattering results for crystalline Li x Si y compounds. The expermental results were compared with theoretical data obtained from DFT calculations . Heyns and Harden reported the temperature dependence of the Raman spectra of chromium‐doped titanite (CaTiOSiO 4 ).…”
Section: Introductionmentioning
confidence: 99%